Placental blood flow in progesterone deficiency - D. Valsky; Yu.E. Dobrokhotova; E.A. Zubareva; Borovkova E.I; S.A. Zalesskaya; S.N. Каzantsev (LCC «Medicine-Inform», 2019)
D. Valsky1, Yu.E. Dobrokhotova2, E.A. Zubareva2, E.I. Borovkova2, S.A. Zalesskaya2, S.N. Каzantsev2 1Hadassah University Hospital, Jerusalem, Israel 2Pirogov Russian National Research Medical University, Moscow, Russian Federation Aim: to assess the effect of progesterone deficiency in the first trimester of pregnancy on the parameters of placental blood flow of the developing placenta. Patients and Methods: 97 women with monocyesis, uterine pregnancy (6-8 weeks) were enrolled in the study. Progesterone concentration was measured twice with the 2-week interval by chemiluminescence immunoassay in serum from venous blood samples. Ultrasound was performed between weeks 11-13 and weeks 16-18 to assess fetus and placenta. Placental blood flow was evaluated using Superb Microvascular Imaging (SMI) technology provided by Aplio™ 500 ultrasound system (Canon Medical Systems). Correlation analysis was performed to study the relationship between serum progesterone levels and placental blood flow parameters. All women were followed-up until the end of pregnancy. Results: all women were subdivided into two groups depending on progesterone levels, i.e., study group (low blood progesterone levels, n=67) and control group (normal blood progesterone levels, n=30). Superb Microvascular Imaging technology has demonstrated poor blood circulation and single vascular bundles on the whole surface of the tested area of developing placenta in the study group and abundant vascular network in the control group. Conclusions: reduced progesterone levels in the first trimester of pregnancy is among the factors contributing to the development of pathological placent al vascular network. SMI technology and calculation of vascular index evaluate placental hemodynamics. Keywords: pregnancy, placental blood flow, microvascular network, progesterone, SMI, Aplio™ 500. For citation: Valsky D., Dobrokhotova Yu.E., Zubareva E.A. et al. Placental blood flow in progesterone deficiency. Russian Journal of Woman and Child Health. 2019;2(3):164-167.